Copolymerization of recombinant Phascolopsisgouldii hemerythrin with human serum albumin for use in blood substitutes. (17th February 2017) - Arkosi, Mariann; Scurtu, Florina; Vulpoi, Adriana; Silaghi-Dumitrescu, Radu; Kurtz, Donald
Abstract: Hemerythrin is an oxygen-carrying protein found in marine invertebrates and may be a promising alternative to hemoglobin for use in blood substitutes, primarily due to its negligible peroxidative toxicity. Previous studies have shown that glutaraldehyde-induced copolymerization of hemoglobin with bovine serum albumin increases the half-life of the active oxy form of hemoglobin (i.e. decreases the auto-oxidation rate). Here, we describe a protocol for glutaraldehyde copolymerization of Hr with human serum albumin and the dioxygen-binding properties of the co-polymerized products. The copolymerization with HSA results in alteration of hemerythrin's dioxygen-binding properties in directions that may be favorable for use in blood substitutes.